The Influence of Using Ice Breaking on Students' Interest in Learning the Al-Quran and Hadith Subject in Madrasahs - Muhammad Kamil Nasution; Muh Zacky Fadhil Rachmat (Yayasan Zia Salsabila, 2026)
This study aims to determine the effect of ice breaking on students’ learning interest in Al-Qur’an Hadist subject for seventh-grade students at MTsN 4 Tapanuli Selatan. This research employed a quantitative approach with an experimental method. The population consisted of all seventh-grade students, with a sample of 38 students divided into experimental and control classes. The research instrument was a learning interest questionnaire consisting of 31 items that had been tested for validity and reliability. Data analysis techniques included normality tests, homogeneity tests, and hypothesis testing. The results showed that the average learning interest score in the experimental class was 88, while the control class scored 79. The hypothesis test results indicated a significance value of 0.00 < 0.05, indicating that the use of ice breaking has a significant effect on students’ learning interest.